PENGARUH PEMBERIAN PUPUK ORGANIK CAIR LIMBAH TAPIOKA TERHADAP PERTUMBUHAN TANAMAN KEMANGI (Ocimum sanctum L.) UNTUK SUMBER BELAJAR BERUPA PANDUAN PRAKTIKUM - Eka Novita Sari; Agus Sutanto; Widya Sartika Sulistiani (Prodi Pendidikan Biologi FKIP Universitas Muhammadiyah Metro, 2021)
The aim of this study are 1) to determine the effect of tapioca waste liquid organic fertilizer on basil plants, 2) to find out the most influential volume percentages, 3) to find out the study results can be used as practical teaching materials. This type of research is an experiment using a completely randomized design (CRD).This study contained 4 treatments namely, 3 treatments giving different types of tapioca waste liquid organic fertilizer which differed namely 40 ml, 50 ml and 60 ml. The parameters observed in this study were height of the plant (cm) and number of leaves.Based on the study result it can be concluded that there was a real effect of tapioca waste liquid organic fertilizer application on the growth of basil plants including plant height and the number of leaves, based on the analysis of Anava test was obtained Fvalue> Ftable. The best treatment in this study was treatment with a volume of 60 ml.The results of this study can be used as a learning biology source at XII grade on the growth and development material in the form of practical guidelines.